PENGEMBANGAN GAME EDUKASI UNTUK MATERI BANGUN DATAR MENGGUNAKAN LINTASAN BELAJAR GEOMETRI - Budhayanti, Clara Ika Sari; Bata, Julius (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
Mathematics is an essential subject for students to master from the start. However, most students have difficulty learning mathematics and reduce interest in learning. This is one of the causes of low math test results. Therefore, a learning method or media was needed that can attract students' interest in learning. One of the learning media that can attract students' interest in educational games. This study aims to develop educational games that can be needed as a medium for learning mathematics, primarily material about geometry. The research method used in this research is development research. The geometry learning path is used as the basis for game design. The trial was conducted with a small group involving teachers and students. The game was developed using the Unity 3D game engine with a digital storytelling model in the geometry learning pathway in elementary schools. The results of the development show that the educational game with the name "GEMBIRA" can help improve the ability to learn flat shapes. This game can also help the learning process of students who experience learning trajectories based on Piaget and Van Hiele's learning trajectories. The game "GEMBIRA" can also attract students' attention to complete all the games, so that students can gain complete knowledge and understanding of the concept of flat shapes. Teachers are advised to use the game "GEMBIRA" in the learning process, especially learning material for flat shapes. It is suggested for learning media developers, especially educational game developers, to develop educational games by referring to the learning trajectory that students must pass so that the games developed can complement the learning process at school. Matematika merupakan mata pelajaran yang penting untuk dikuasai oleh siswa sejak awal. Namun, sebagian besar siswa mengalami kesulitan belajar matematika dan mengurangi minat belajar. Hal ini menjadi salah satu penyebab hasil tes matematika cenderung rendah. Oleh karena itu, dibutuhkan cara atau media pembelajaran yang dapat menarik minat belajar dari siswa. Salah satu media pembelajaran yang dapat menarik minat siswa adalah game edukasi. Penelitian ini bertujuan untuk mengembangkan game edukasi yang dapat digunakan sebagai media pembelajaran matematika khususnya materi tentang geometri. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian pengembangan. Lintasan belajar geometri digunakan sebagai dasar untuk merancang game. Uji coba dilakukan dengan small group yang melibatkan guru dan siswa. Game dikembangkan dengan menggunakan game engine Unity 3D dengan model digital storytelling dalam lintasan belajar geometri di sekolah dasar. Hasil pengembangan menunjukkan bahwa game edukasi dengan nama “GEMBIRA” dapat membantu meningkatkan efektivitas pembelajaran bangun datar. Game ini juga dapat membantu proses belajar siswa yang mengalami lompatan tahapan pembelajaran berdasarkan lintasan belajar Piaget dan Van Hiele. Selain itu, game “GEMBIRA” juga dapat menarik perhatian siswa untuk menyelesaikan seluruh game, sehingga siswa dapat memperoleh pengetahuan dan pemahaman yang utuh mengenai konsep bangun datar. Guru disarankan untuk menggunakan game “GEMBIRA” dalam proses pembelajaran, khususnya pembelajaran materi bangun datar. Selain itu juga disarankan bagi para pengembang media pembelajaran khususnya pengembang game edukasi, untuk mengembangkan game-game edukasi dengan mengacu pada lintasan belajar yang harus dilalui siswa sehingga game yang dikembangkan dapat melengkapi kekurangan proses pembelajaran di sekolah.